Centrifuge model tests on the near-horizontal slide of hard soil-soft rock landslides - HU Le; XIN Peng; WANG Tao; LIANG Changyu; LI Congan (Dizhi lixue xuebao, 2021)
In order to study the deformation characteristics of the Neogene hard soil-soft rock landslides in northwest China, two sets of centrifuge model tests were conducted to simulate the deformation process under the degraded state of shear zones, and the soil pressure and displacement-time curve during the deformation process of the landslides were obtained. The test results reveal that when the strength of the soft zone decreases, the main body of the hard soil-soft rock landslide is block-like. In the process of fast slide, the slip mass presents an overall translational slide, without complete liquefaction and disintegration. The attenuation of the dynamic friction strength of the slide zone is the main controlling factor in the distance and time of the movement. Moreover, the slide zones of hard soil-soft rock landslides with high stress underwent plastic flow deformations, which caused the horizontal stress concentration in the front part of the landslide, resulting in the horizontal movement of the overlying slip mass in the front part of the landslide and the extension to the back edge of the landslide, and multi-level horizontal slides occurred at the end.